Numerical Simulation of Pile Group Response in Slope Layered Soil under the Effect of Seismic Loading (Journal of Engineering, 2023)
This work investigates the effect of earthquakes on the stability of a collective pile subjected to seismic loads in the soil layer. Plaxis 3D 2020 finite element software modeled pile behavior in dry soils with sloping layers. The results showed a remarkable fluctuation between the earthquakes, where the three earthquakes (Halabja, El Centro, and Kobe) and the acceleration peak in the Kobe earthquake had a time of about 11 seconds. Different settlement results were shown, as different values were recorded for the three types of earthquakes. Settlement ratios were increased by increasing the seismic intensity; hence the maximum settlement was observed with the model under the effect of the Kobe earthquake (0.58 g), where subsidence values at the three tremors differed between the pile distribution pattern. The highest drop recorded by the results was 60 mm in a distribution pattern 2×3. In general, increasing the size of the cap leads to an additional drop due to the weight of the cap.